The impact of agricultural machinery services on cultivated land productivity and its mechanisms: A case study of Handan city in the North China plain - Liu, Yan; Shi, Xiaoping; Gao, Fugang (Frontiers in Environmental Science, 2022)
Abstract: Studying the impact of agricultural machinery services (AMS) on cultivated land productivity is conducive to scientifically improving agricultural production and has far-reaching significance for ensuring food security. Taking Handan City in the North China Plain as the research context and using a surveyed sample of 1918 farming households, this paper examines the effect of AMS on the productivity of cultivated land using OLS estimation and estimates the average treatment effect on the treated (ATT) using the propensity score matching (PSM) method. The research findings are as follows. 1) AMS has a significantly positive impact on cultivated land productivity, and a heterogeneity analysis finds that the effects are larger for farmers with relatively less cultivated land and the marginal effects decrease as the adoption of AMS increases. 2) In various planting activities, AMS adoption in basic activities (e.g., ploughing, seeding, and harvesting) has positive effects on cultivated land productivity, while AMS adoption in management activities (e.g., fertilizing, irrigation, and pesticide spraying), has no obvious effect on cultivated land productivity. 3) According to the results of ATT, the conversion of non-adopting farmers to adopting AMS would increase cultivated land productivity by 7.6% to 12.1%. 4) A mechanism analysis reveals that AMS adoption relieves financial constraints, improves technical efficiency, and increases smallholders’ crop yields. These results suggest that AMS has a positive effect on cultivated land productivity and therefore have valuable policy implications for increasing smallholders’ access to various types of AMS to improve the productivity of cultivated land in regions dominated by smallholders.